Innovation Management: A Bibliometric Analysis of 50 Years of Research Using VOSviewer® and Scopus - José Manuel Saiz-Alvarez (World)
Using the bibliometric software VOSviewer® version 1.6.20 and Scopus as a bibliographic database, this paper aims to investigate the research streams in terms of the co-occurrence network of authors, terms extracted from the title field, countries, keywords, and organizations researching on IM from publications between 1974 and 2024. Retrieved from Scopus and using science mapping bibliometric techniques with VOSviewer®, 4756 documents published on IM from 1974 to 2024 were analyzed, divided in three phases (1974–1995, 1996–2019, and 2020–2024), and limited to BMA (Business, Management, and Accounting), EEF (Economics, Econometrics, and Finance), and SOC (Social Sciences). The main findings are as follows: (a) there is a tendency for a minimal relationship between authors from different organizations and countries to collaborate in research on IM; (b) almost half (45.12%) of the publications on IM were published by authors from the European Union, which rises to 55.24% in Europe if the United Kingdom is included. These results are far ahead of those of the United States (13.4%), China (7.6%), the Russian Federation (3.6%), and Japan (2.3%). (c) While the first publications on IM deal with aspects related to product development, management, technology, R&D, and competition, there is a recent trend to link IM to sustainable development, open innovation, ecosystems, stakeholders’ engagement, and entrepreneurship.